Synthesis of palm oil-based epoxidized trimethylolpropane esters as oxidatively stable lubricant - Naidir, Ferra (2011)
The main objective of this study is to improve the oxidative stability of trimethylolpropane ester (TMP ester) by modifying the unsaturated fatty acids structure of TMP ester through an in-situ epoxidation reaction. The in-situ epoxidation reaction of TMP ester was conducted to produce epoxidized trimethylolpropane ester (epoxidized TMP ester). The synthesis takes place by the reaction of a carboxylic acid (acetic acid: CH3COOH) as the oxygen carrier with concentrated hydrogen peroxide (H2O2) as the primary source of oxygen to produce a percarboxylic acid (peracetic acid) as an epoxidizing agent. A small amount of sulfuric acid catalyst was used to speed up the reaction to form peracetic acid. The effects of CH3COOH concentration, H2O2 concentration, temperature, reaction time and the catalyst were investigated to obtain the optimum yield of oxirane ring at 3.92%. The highest percentage of oxirane oxygen was obtained when the epoxidation was carried out using molar ratio of CH3COOH/ H2O2 at 1 : 5.5 mol, 50 oC oftemperature, 2 h reaction time, and 2% (w/w) of catalyst. Fourier transform infrared (FTIR) spectra showed the formation of epoxy group at the wave number of 824 cm-1. A central composite design (CCD) technique was used to determine the optimum conditions for the epoxidation of palm oil-based TMP ester. Four independent variables were applied (concentration of CH3COOH, concentration of H2O2, temperature, and reaction time) to correlate with three responses (percentage of oxirane oxygen, iodine value, and hydroxyl value). The optimum values of percentage of oxirane oxygen, iodine value, and hydroxyl value were 4.01, 1.94, and 0.43%, respectively under the following operation conditions; 0.59 mol of CH3COOH concentration, 7.5 mol of H2O2 concentration, temperature at 50 oC and reaction time of 7 h. The kinetics of epoxidation of palm oil-based TMP esters was studied based on the assumptions of pseudo first order and second order mechanisms. The kinetic study was conducted to cover two regions of temperatures namely low temperatures region (30, 50, and 60 oC) and high temperature region (70, 80, and 90 oC). The rate constants for pseudo first order rate model for low and high temperatures in the range of 30-60 oC and 70-90 oC were 9 x 10-4 – 5.5 x 10-3 and 1.29 x 10-2 - 2.09 x 10-2 h-1, respectively. The rate constants for second order rate model for low and high temperature regions were 1.3 x 10-3 - 1.55 x 10-2 and 0.03 - 8.37 x 10-2 l mol-1h-1, respectively. The activation energies for second order model were 69.4 and 53.3 kJ mol-1 for low temperature and high temperature region respectively. The activation energies value indicated that the reaction easy to take place at high temperature. The kinetics of oxidative degradation for epoxidized TMP ester, TMP ester, and commercial oil (cooking oil) was also investigated. This was carried out using differential scanning calorimetry (DSC) to analyze the rate of oxidation where is the data was obtained at a heating rate of 5 oC/min. The result showed that the onset temperature for oxidation for both of TMP ester and cooking oil was at 170 oC while for epoxidized TMP ester, it was slightly higher at a temperature of 187 oC. The activation energy for oxidation was calculated using Ozawa Flynn Wall method where is the values for epoxidized TMP ester, TMP ester, and cooking oil were 112.89, 78.28, and 75.45 kJ/mol, respectively. These results showed that the oxidative stability of TMP esters has been improved significantly by epoxidation of TMP esters. The lubrication properties of epoxidized TMP ester also indicated good potential as a base stock for lubricant formulation due to the marked improvement in lubricating characteristic compared to TMP ester. Although the pour point increased slightly but other lubrication properties are better than the properties of most vegetable oil-based commercial base oils.